2019
DOI: 10.1101/572602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ER membrane protein complex is required to ensure correct topology and stable expression of flavivirus polyproteins

Abstract: 11Flaviviruses translate their genomes as multi-pass transmembrane proteins at the endoplasmic 12 reticulum (ER) membrane. Here, we show that the ER membrane protein complex (EMC) is 13 indispensable for the expression of viral polyproteins. We demonstrated that EMC was essential 14 for accurate folding and post-translational stability rather than translation efficiency. Specifically, 15we revealed degradation of NS4A-NS4B, a region rich in transmembrane domains, in absence of 16 EMC. Orthogonally, by serial p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The role of the EMC during the co-translational biogenesis of multi-span TMPs is not strictly limited to protein clients whose first TMD is type III-like (Fig. 4A), additionally extending to the stabilisation and/or insertion of downstream TMDs [99][100][101]112,113] irrespective of the orientation of the first TMD [89,90]. The decisive feature for the EMC-dependence of these multi-span TMPs is reduced hydrophobicity and/or increased polarity or charge, as further evidenced by the ability to create artificial EMC dependency by introducing polar/charged residues into a TMD [90,99,100].…”
Section: Membrane Insertion Via the Emcmentioning
confidence: 99%
“…The role of the EMC during the co-translational biogenesis of multi-span TMPs is not strictly limited to protein clients whose first TMD is type III-like (Fig. 4A), additionally extending to the stabilisation and/or insertion of downstream TMDs [99][100][101]112,113] irrespective of the orientation of the first TMD [89,90]. The decisive feature for the EMC-dependence of these multi-span TMPs is reduced hydrophobicity and/or increased polarity or charge, as further evidenced by the ability to create artificial EMC dependency by introducing polar/charged residues into a TMD [90,99,100].…”
Section: Membrane Insertion Via the Emcmentioning
confidence: 99%
“…The strategies reported here lay out a roadmap for their identification and validation. Characterization of these assembly factors will reveal how the cell ensures the stoichiometric assembly of intricate molecular machines in the crowded cellular milieu, and provide insight into how these processes may fail leading to disease (Harper and Bennett, 2016;Oromendia and Amon, 2014). (A) FLAG-tagged WNK1 and its truncations were tested for binding to EMC2 (see methods).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed biochemical reconstitution experiments have shown that the EMC can both cotranslationally insert TMDs in the Nexo-topology, and post-translationally insert tailanchored proteins with TMDs of moderate hydrophobicity (Chitwood et al, 2018;Guna et al, 2018). Proteomic interrogation of EMC function also suggests it plays a role in stabilizing multi-pass membrane proteins, including many viral coat proteins (Barrows et al, 2019;Chitwood and Hegde, 2019;Ngo et al, 2019;Shurtleff et al, 2018;Tian et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The strategies reported here lay out a roadmap for their identification and validation. Characterization of these assembly factors will reveal how the cell ensures the stoichiometric assembly of intricate molecular machines in the crowded cellular milieu, and provide insight into how these processes may fail leading to disease (Harper and Bennett, 2016;Oromendia and Amon, 2014).…”
Section: Discussionmentioning
confidence: 99%